Rancang Bangun dan Uji Kinerja Alat Perajang Batang Singkong Tipe TEP-1 - Ridho Al Akbar Gustam; Sandi Asmara; Budianto Lanya; R. A. Bustomi Rosadi (abe.fp.unila.ac.id, 2022)
Cassava stems has not been maximally utilized, its existence in the land other than just thrown away and burned. This condition is the background of the research on the design of cassava stem chopper tool and its performance test. Methods in this study include the design and experiments cassava stems chopper. The chopper performance test was performed by calculating the values of the parameters including the working capacity of the tool (kg/hour), the calculation of the weight loss (%), and the calculation of fuel consumption (ℓ/hour) tested on the chopper tool while operating at RPM 560, 870 and 1245. From the test, the working capacity are 38,67 kg/hour, 59,73 kg/hour and 78 kg/hour; the weight average 4.60%, 3.89%, and 4.09%; the fuel consumption are 0.27 ℓ/hour, 0.68 ℓ/hour and 0.81 ℓ/hour. For the three chopper size fractions > 0.5 cm, 0,2 <x <0,5 cm, and <0,2 cm, with RPM 560 obtained 12,88%, 45,45% , and 41.47%; for RPM 870 obtained 11.95%, 38.71%, and 49.35%; then for RPM 1245 obtained the result 13.37%, 37.50%, and 49.13%. From the data, it can be concluded that for the best performance capacity obtained at RPM 1245 with the result of working capacity obtained 78 kg / hour with fuel consumption 0,81 ℓ/hour.